2004
DOI: 10.1111/j.1468-3083.2004.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular bipenicillin vs. intravenous penicillin in the treatment of erysipelas in adults: randomized controlled study

Abstract: The objective of the study was to evaluate the efficacy of intramuscular penicillin: mixture of benzyl penicillin and procain penicillin (2 MU x 2 times daily) and intravenous benzyl penicillin (4 MU x 6 times daily) in the treatment of hospitalized adult patients with erysipelas. A prospective randomized unicentric trial was conducted. In total, 112 patients entered the study; 57 in the intramuscular group and 55 patients in the intravenous group completed the trial. The failure rate was 14% for intramuscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Patients who showed local or general state complication during the 10 days of treatment or who did not have clinical improvement at the 10th day of treatment were considered treatment failures and left the trial. The investigators found no difference in the cure rate (failure rate 14% IM, 20% IV; absolute risk difference 6%, P = 0.40) or local complications (9.1% IV, 7% IM; P = 0.477), but 26% had venous inflammation in the IV group [31]. The IV and IM routes were thus equally effective, but there was less treatment-related morbidity with IM penicillin.…”
Section: Prospective Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Patients who showed local or general state complication during the 10 days of treatment or who did not have clinical improvement at the 10th day of treatment were considered treatment failures and left the trial. The investigators found no difference in the cure rate (failure rate 14% IM, 20% IV; absolute risk difference 6%, P = 0.40) or local complications (9.1% IV, 7% IM; P = 0.477), but 26% had venous inflammation in the IV group [31]. The IV and IM routes were thus equally effective, but there was less treatment-related morbidity with IM penicillin.…”
Section: Prospective Studiesmentioning
confidence: 92%
“…Previous evidence-based reviews have found no satisfactory randomized studies of antibiotics versus placebo or of IV antibiotics versus the same agent given orally [8], although one such study exists for IV versus intramuscular (IM) administration of penicillin [31]. There are some published summaries of head-to-head comparisons.…”
Section: Evidence Summarymentioning
confidence: 99%
“…Penicillin, which is inactive against most S aureus isolates, has been quite successful in treating lower limb cellulitis in various series, 3,4,46,48,50 and in most studies has been about as efficacious as agents active against both streptococci and S aureus when directly tested in randomized trials or when success rates are compared in different series. 5,[62][63][64][65][66] The role of MRSA in causing lower extremity cellulitis seems quite small. In one prospective trial of ''nonculturable cellulitis,'' for example, antibiotics effective against methicillinsusceptible S aureus (MSSA)-but not MRSA-had a 96% cure rate in a hospital where other types of MRSA soft-tissue infections were common.…”
Section: Predisposing Factors Key Pointsmentioning
confidence: 98%
“…One study 56 (n = 112) compared IV benzylpenicillin with intramuscular penicillin (benzylpenicillin and procaine penicillin) for 10 days. No difference in outcome was observed (RR = 0.93; 95% CI, 0.79-1.10) (eFigure 9.7.1 in the Supplement), but more adverse events occurred in the IV group (RR = 7.25; 95% CI, 1.73-30.45; P = .007) (eFigure 9.7.2 in the Supplement).…”
Section: Other Studies Not Already Includedmentioning
confidence: 99%
“…Eleven studies 15,19,24,[29][30][31]40,44,54,58 were described as open, with 5 additional studies presumed to be not blinded (their design was not specified). 25,27,28,50,56 This lack of blinding, in combination with a lack of objective outcome measures, could increase the risk of bias. 11…”
Section: Limitationsmentioning
confidence: 99%